INFLUENCE OF GROWTH STIMULANTS ON PRODUCTIVITY OF SPRING BARLEY VARIETIES - Korotkova, I. V.; Gorobets, M. V.; Chaika, T. O. (Scientific Progress & Innovations, 2021)
Timely and reliable forecasting of grain yields is the main condition for effective crop management. In this study, we evaluated the effect of Epin-extra, Zircon and Bischofite natural growth stimulants on the duration of the main vegetation phases of Helios, Vakula and Parnas spring barley varieties of Ukrainian selection. In regard with this purpose, during three years (2017–2019) field studies were conducted aimed at revealing the most effective growth stimulant for cultivating different varieties of spring barley under unstable moistening. It has been found that pre-sowing seed treatment and spraying of crops in the tillering phase with these stimulants lead to reducing vegetation phases and increasing the crop’s photosynthetic activity. The research was conducted in the production conditions of the farm “Gorobets S. G.” of Reshetylivka district, Poltava region. We evaluated the factors of affecting growth stimulants and bischofite natural mineral on the net productivity of photosynthesis, photosynthetic potential of spring barley crops and leaf-area duration of barley plants. The treatment with growth stimulants was conducted before sowing directly on the seeds and spraying the crops – in the tillering phase. Epin-extra and Zircon stimulants were used at a rate of 50 g/ha, and Bischofite – 2 l/ha. The area of the experimental field was 100 hectares. When treating spring barley crops with growth stimulants on typical black soils, the best indicators of net photosynthesis productivity were in spring barley varieties after their treatment with 1 % bischofite solution. In comparison with the control in the variants with the use of stimulants, the duration of the vegetation period was reduced as well as the beginning of the corresponding phases of development. The maximum effect was observed at using 1 % water solution of Bischofite. Crop treatment with this preparation favored the increase in the plants’ assimilation leaf-area duration by 11.1 %, the value of photosynthetic potential – by 5.7 % and the crops’ photosynthesis productivity – by 10 %. When spraying spring barley crops in the tillering phase with Epin-extra, Zircon and Bischofite growth regulators on sod-podzolic soil, the duration of plant development phases was reduced, therefore, the growing period decreased by 2–4 days, which allows start harvesting spring barley grain earlier than usual.